Three hours in Paris - Black, Cara, 1951- (New York, NY : Soho Crime, 2020)
"The story of Kate Rees, the young American markswoman who has been recruited by British intelligence to drop into Paris on the dangerous business of trying to assassinate the Fuhrer. A country girl from rural Oregon--a grieving widow with no spy training, but a vendetta and a lot of gumption--now has the state of the entire war in her hands. When the hit goes badly wrong, Kate is on the run for her life--all the time wrestling with the suspicion that the whole operation was a set-up"--
Color map on endpapers.
"A novel"--Jacket.
Keywords: World War, 1939-1945 -- Secret service -- France -- Paris -- Fiction; Female assassins -- Fiction; Women spies -- Fiction; Americans -- France -- Paris -- Fiction; Widows -- Fiction; Spy fiction; Paris (France) -- Fiction; Spy fiction; Historical fiction